ANALYSIS OF COMPANY FINANCIAL PERFORMANCE USING DU PONT SYSTEM METHOD AT PT. ANEKA TAMBANG (PERSERO) DURING THE PANDEMIC AND BEFORE THE COVID-19 PANDEMIC - Helmalia Hardiyanti; Tommy Kuncara; Herry Sussanto (Asosiasi Dosen Muda Indonesia, 2022)
This study aims to measure the company's financial performance by using the Du Pont System at PT. Aneka Tambang (Persero) During the Pandemic and Before the Covid-19 Pandemic. The method used in this study is the Du Pont System method using the ratio Net Profit Margin (NPM), Total Assets Turnover (TATO), Return On Invesment (ROI), Equity Multyplier (EM), dan Return On Equity (ROE) from secondary data obtained from www.antam.com/ which is the official site of PT. Aneka Tambang (Persero) Tbk. Based on the results of calculations using Du Pont System shows that financial performance PT. Aneka Tambang (Persero) During the Pandemic and Before the Covid-19 Pandemic, it was considered not good because ROE which has decreased. ROE which decreased due to the value of ROI which decreased by 2,78% and the decreasing EM value by 0,08 time. ROI which decreased due to the decreasing NPM value and the decreasing TATO value by 0,22 time. While the declining value of EM is due to the fact that the company is less than optimal in generating total assets from total equity. In this case, the higher the value of Equity Multiplier the more external funds or debt the company uses to fund company activities.